Outbreak of human infection with Sarcocystis nesbitti, Malaysia, 2012 - AbuBakar, Sazaly; Teoh, B.T.; Sam, S.S.; Chang, L.Y.; Johari, J.; Wong, K.T.; Ramli, Norlisah; Hooi, P.S.; Lakhbeer-Singh, H.K.; Italiano, C.M.; Syed Omar, S.F.; Tan, C.T. (Centers for Disease Control and Prevention, 2013)
An outbreak of fever associated with myalgia and myositis occurred in 2012 among 89 of 92 college students and teachers who visited Pangkor Island, Malaysia: The Sarcocystis nesbitti 18S rRNA gene and sarcocysts were obtained from muscle tissues of 2 students. Our findings indicate emergence of S. nesbitti infections in humans in Malaysia.